Online short videos promoting public breast cancer literacy: a pretest-posttest control group trial on efficiency, attitude, and influencing factors - Xu, Qian-Rui; Wu, Pei-Zhu; Du, Jia-Zi; Zhuang, Wen-Jun; He, Xiao-Tong; Ma, Yong-Yong; Zeng, De; Liang, Yuan-Ke; Xu, Xiao-Yang; Xie, Lei; Lin, Hao-Yu (Frontiers in Public Health, 2023)
Background Short videos on social media are playing an increasingly important role in cancer health education today. It is important to explore how the actual communication effect of health videos and the knowledge absorption of users are influenced by different factors of the video creation process. Objective The objective of our study is to access the factors influencing breast cancer health education through short videos on efficiency and quality. Methods Three pairs of videos about breast health were created and participants completed questionnaires before and after watching the videos. A paired t-test was used to analyze within-group change scores. RM-ANOVA was used to assess the relationship between the pretest, posttest, and three variables. Results Watching short videos can significantly increase viewers’ knowledge of related health topics (p < 0.05). The viewers’ concentration level while watching was significantly higher for the video with background music (BGM) than for the video without BGM (p = 0.006). The viewers’ willingness to share was significantly higher for the video with a progress bar than for the video without a progress bar (p = 0.02). Using an interpreter wearing a doctor’s uniform instead of casual wear and setting a progress bar can significantly improve the efficiency of knowledge absorption (p < 0.05). Conclusion A uniformed interpreter, BGM and a progress bar are factors influencing the efficiency of short health videos. They can be applied in video making to explore better ways of promoting cancer health education in the new mobile Internet environment.